2020
DOI: 10.1111/joim.13149
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Vitamin D deficiency and COVID‐19 severity – plausibly linked by latitude, ethnicity, impacts on cytokines, ACE2 and thrombosis

Abstract: Background SARS‐CoV‐2 coronavirus infection ranges from asymptomatic through to fatal COVID‐19 characterised by a “cytokine storm” and lung failure. Vitamin D deficiency has been postulated as a determinant of severity. Objectives To review the evidence relevant to vitamin D and COVID‐19 Methods Narrative review Results Regression modelling shows that more northerly countries in the Northern Hemisphere are currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
217
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(247 citation statements)
references
References 128 publications
(162 reference statements)
7
217
0
23
Order By: Relevance
“…In this context, vitamin D's dual roles of initially controlling viral replication and later dampening the hyper-inflammation are tantalising. This is consistent with the observation that low levels of vitamin D (or indeed polymorphisms in the VDR) may adversely impact the outcome of patients with COVID-19 [17,[24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 88%
“…In this context, vitamin D's dual roles of initially controlling viral replication and later dampening the hyper-inflammation are tantalising. This is consistent with the observation that low levels of vitamin D (or indeed polymorphisms in the VDR) may adversely impact the outcome of patients with COVID-19 [17,[24][25][26][27][28][29][30].…”
Section: Resultssupporting
confidence: 88%
“…More recently, another study reported a highly significant, positive correlation between lower death rates and a country’s proximity to the equator [ 179 ]. Rhodes et al described that more northerly countries are currently showing relatively high COVID-19 mortality, with an estimated 4.4% increase in mortality for each 1-degree latitude north of 28 degrees North [ 180 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In light of accruing evidence that vitamin D3 status is inversely correlated with severity of COVID-19 ( 23 26 ), it is significant that, via its hormone-like actions on gene expression, D3 has been shown to be a potent activator of both TXNRD1 and GCLC. In a microarray study, 6 h after exposure to 1,25-dihydroxyvitamin D3, TXNRD1 mRNA was upregulated 7.1X, and GCLC was upregulated 2.5X ( 27 ).…”
Section: The Potential M Pro Targets Txnrd1 and Gcmentioning
confidence: 99%